Challenges in Gender Mainstreaming in the Department of Education: Basis for Proposed Intervention Program for Secondary Teachers in the Division of Zambales - Sepillo, Jesseca Jean A.; Orge, Novrina Bigilda A. (Future Science / FSH-PH Publications, 2021)
The study aimed to determine the challenges in gender mainstreaming in the Department of Education. The study made use of descriptive research design with the aid of questionnaires the main instrument in gathering the data. Descriptive and inferential statistics were used for data analysis. The study revealed that a typical respondent was in their middle adulthood aged thirty-one to forty, majority were female, most have rendered zero to four years in service, more than half of the public secondary teachers are Teacher I, and most of the public secondary teachers attended three to five numbers of relevant training on gender mainstreaming. The public secondary teachers identified that the security, health and other student services was moderately serious problem while facilities, administration, instruction and curriculum was not a problem. There was a statistically significant difference on the problems encountered by the public secondary teachers on the gender mainstreaming implementation in terms of administration and curriculum when grouped according to age and number of relevant training attended on gender mainstreaming. There was a statistically significant difference on the problems encountered by the public secondary teachers on the gender mainstreaming implementation in terms of instruction when grouped according to number of relevant training attended on gender mainstreaming. There was a significant difference on the problems encountered by the public secondary teachers on the gender mainstreaming implementation in terms of facilities when grouped according to sex, length of service and number of relevant training attended on gender mainstreaming. There was a significant difference on the problems encountered by the public secondary teachers on the gender mainstreaming implementation in terms of security, health and other student services when grouped according to sex and number of relevant training attended on gender mainstreaming. The proposed intervention program addresses the gender mainstreaming implementation for public secondary teachers in the Division of Zambales